Penelitian Hukum: Dari Monodisipliner Ke Interdisipliner - Ricardo Simarmata (Fakultas Hukum Universitas Mulawarman, 2007)
More than successfully matching the doctrinal law science and social science, the studies of socio-legal keep the distance between both closer. A way to do this seems through suggesting for the social sciences, like sociology, to avoid from the allergy against studying the doctrine and content of law. Law sociology contributes to the explanation of the nature of law through its empirical studies. Any contributions from the legal ideas actually emanate from the law philosophy. Instead, the doctrinal law science needs to develop the review on law texts using theories or concepts of social sciences. Such steps become trustable since the legal rules appear away from the previous simplicity, following the more developed regulatory rules. Key words: penelitian hukum doktrinal (doctrinal legal research), ilmu sosial (social science), penelitian hukum sosial (socio-legal studies).